Climate and construction delays: case study in Chile. Issue 6 (16th November 2015) - Ballesteros-Pérez, Pablo; del Campo-Hitschfeld, Maria Luisa; González-Naranjo, Manuel Alejandro; González-Cruz, Mari Carmen
Abstract : Purpose: – Construction projects usually suffer delays, and the causes of these delays and its cost overruns have been widely discussed, the weather being one of the most recurrent. The purpose of this paper is to analyze the influence of climate on standard construction work activities through a case study. Design/methodology/approach: – By studying the extent at which some weather variables impede outdoor work from being effectively executed, new maps and tables for planning for delays are presented. In addition, a real case regarding the construction of several bridges in southern Chile is analyzed. Findings: – Few studies have thoroughly addressed the influences of major climatic agents on the most common outdoor construction activities. The method detailed here provides a first approximation for construction planners to assess to what extent construction productivity will be influenced by the climate. Research limitations/implications: – Although this study was performed in Chile, the simplified method proposed is entirely transferable to any other country, however, other weather or combinations of weather variables could be needed in other environments or countries. Practical implications: – The implications will help reducing the negative social, economic and environmental outcomes that usually emerge from project delays. Originality/value: – Climatic data were processed using extremely simple calculations to create a series of quantitative maps and tables that would be useful for any construction planner to decide the best moment of the year to start a project and, if possible, where to build it.